258 Deficits in growth, muscle mass, and body composition following intrauterine growth restriction persisted in lambs at 60 d of age but were improved by daily clenbuterol supplementation. (30th November 2020) - Gibbs, Rachel L; Swanson, Rebecca M; Beard, Joslyn K; Schmidt, Ty B; Petersen, Jessica L; Yates, Dustin T
Abstract: Intrauterine growth restriction (IUGR) reduces neonatal muscle growth and alters body composition in livestock. Our objective was to determine the effect of IUGR on juvenile growth and assess the benefits of treatment with clenbuterol (β2 adrenergic agonist) in IUGR offspring. Heat stress-induced IUGR lambs were born 28% lighter (P < 0.05) than controls. At 60 d of age, unsupplemented IUGR lambs had reduced (P < 0.05) bodyweight (BW), average daily gain, and crown-rump length compared to controls, but clenbuterol-supplemented IUGR lambs did not differ from controls. Crown circumference, body girth, and cannon bone length did not differ among groups. Bioelectrical impedance in live lambs and carcasses estimated that lean mass and mass of multiple muscle groups were reduced (P < 0.05) in unsupplemented IUGR lambs but not clenbuterol-supplemented IUGR lambs compared to controls. Estimated protein, fat, and protein/fat were likewise reduced (P < 0.05) in unsupplemented but not clenbuterol-supplemented IUGR lambs. Loin-eye area in chilled carcasses was 30% smaller (P < 0.05) in unsupplemented IUGR lambs but 19% larger (P < 0.05) in clenbuterol-supplemented IUGR lambs compared to controls. Proximate analysis revealed greater (P < 0.05) fat and reduced (P < 0.05) protein and protein/fat in loin muscles from unsupplemented but not clenbuterol-supplemented IUGR lambs compared to controls. At necropsy, hindlimbs, hearts, and flexor digitorum superficialis muscles tended to be lighter (P ≤ 0.09) and lungs and kidneys were lighter (P < 0.05) in IUGR lambs. Kidney weight was further reduced (P < 0.05) in clenbuterol-supplemented IUGR lambs. Brain/BW tended to be reduced (P ≤ 0.09) and lung/BW and kidney/BW were reduced (P < 0.05) in IUGR lambs, but lung weight and lung/BW were greater (P < 0.05) in clenbuterol-supplemented compared to unsupplemented IUGR lambs. We conclude that poor growth and asymmetric body composition previously observed in IUGR neonates persists in juveniles, but daily treatment with clenbuterol recovered growth and improved body composition in IUGR lambs.